Penegakan Hukum Tindak Pidana Pembakaran Hutan di Wilayah Kabupaten Kotawaringin Timur - Aji Prasetyo, , Pujiyono*), Amiek Soemarmi (Diponegoro Law Journal, 2013)
Forest is a natural resources having highly strategic position as it contains abundant natural wealth. The forest devastation causing the worst damage is forest fire. In East Kotawaringin District, Central Kalimantan, forest fires occurs each year. The law enforcement for criminal case of forest fire is required to minimize forest fires caused by humans.            The aims of this research were to recognize the law enforcement for criminal case of forest fire occurred in East Kotawaringin District and what obstructions emerged in the law enforcement of such crime. This research used the method of normative juridical approach. The research specification used in this research was analytical descriptive which describes all symptoms and facts as well as analyzing present problems in relation with the law enforcement for criminal case of forest fire in East Kotawaringin District.